Implementation of axis-aligned bounding box for OpenGL 3d virtual environment - Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Abd Aziz, Mohamad Zoinol Abidin; Bade, Abdullah (Asian Research Publishing Network (ARPN), 2015)
This paper describes a simple and straight forward implementation of Axis-Aligned Bounding-Box (AABB) for OpenGL 3-Dimensional (3D) virtual environment for games and simulation purpose. The implementation of AABB is conducted in OpenGL graphic library version 1.2 with C++ programming language by using Visual C++. The implementation could help young and begineer computer graphics student to master the implementation of basic Bounding-Volume (BV) for collision detection and other fields with related to the Axis-Aligned Bounding-Box (AABB).